Clinicopathologic and Molecular Features of a Series of 41 Biphenotypic Sinonasal Sarcomas Expanding Their Molecular Spectrum. (June 2019) - Le Loarer, François; Laffont, Sophie; Lesluyes, Tom; Tirode, Franck; Antonescu, Cristina; Baglin, Anne-Catherine; Delespaul, Lucile; Soubeyran, Isabelle; Hostein, Isabelle; Pérot, Gaëlle; Chibon, Frédéric; Baud, Jessica; et al.
Abstract : Biphenotypic sinonasal sarcoma (BSNS) is a locally aggressive tumor occurring in the sinonasal region. It harbors both myogenic and neural differentiation and is characterized by PAX3 rearrangement with MAML3 as the most frequent fusion partner, but the partner of PAX3 remains unidentified in a subset of cases. About 70 cases have been reported so far. In this study, we report a series of 41 cases with clinical, pathologic, and molecular description. Twenty-five (61%) patients were female individuals, and the median age was 49 years. Tumors arose predominantly in the nasal cavity and ethmoidal sinuses. Local recurrences occurred in 8 cases of the 25 (32%). Histologic features were characteristic of BSNS, with 5 cases showing focal rhabdomyoblastic differentiation. Immunohistochemistry showed a constant positivity of S100 protein and PAX3 and negativity of SOX10. MyoD1 was focally positive in 91% of cases, whereas only 20% were positive for myogenin. Molecular analysis showed a PAX3-MAML3 transcript in 37 cases (90%). RNA sequencing was performed in the 4 negative cases for PAX3-MAML3 fusion, and it showed that 1 case harbored a PAX3-FOXO1 fusion, as previously described in the literature, and 2 novel fusions: PAX3-WWTR1 fusion in 2 cases and PAX3-NCOA2 fusion in 1 case. RNA sequencing results were confirmed by fluorescence in situ hybridization, reverse transcription-polymerase chain reaction, and Sanger sequencing. The PAX3-NCOA2 -positive case showed focal rhabdomyoblastic differentiation. In conclusion, we report 2 novel fusions ( PAX3-WWTR1 and PAX3-NCOA2 ) in BSNS and show that MyoD1 is more sensitive than myogenin for demonstrating myogenic differentiation in this tumor.